2009
DOI: 10.3354/meps08109
|View full text |Cite
|
Sign up to set email alerts
|

Bycatch and discard mortality in commercially caught blue sharks Prionace glauca assessed using archival satellite pop-up tags

Abstract: Blue sharks Prionace glauca are the most frequently discarded fish species during commercial pelagic longline fishing operations worldwide, yet their post-release mortality rate has never been measured. A generalized linear model of 12 404 blue sharks observed during the Canadian Atlantic pelagic longline swordfishery suggested a hooking mortality of 12 to 13%, yet scientific examination of 902 of these sharks indicated that hooking mortality was actually higher. A random sample of 40 of these blue sharks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(170 citation statements)
references
References 25 publications
6
163
1
Order By: Relevance
“…The smooth hammerhead seems to be a particularly vulnerable species in this respect, as 71% of the specimens are captured already dead. Campana et al (2009) about blue sharks caught by the Canadian longline fishery in the northwest Atlantic Ocean, concluded that short-term hooking mortality was in the 12−13% range (measured by fishery observers), which is very close to our study (14%). However, these authors stated that hooking mortality might be underestimated: it could be around 20% in blue sharks in the Canadian fishery.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The smooth hammerhead seems to be a particularly vulnerable species in this respect, as 71% of the specimens are captured already dead. Campana et al (2009) about blue sharks caught by the Canadian longline fishery in the northwest Atlantic Ocean, concluded that short-term hooking mortality was in the 12−13% range (measured by fishery observers), which is very close to our study (14%). However, these authors stated that hooking mortality might be underestimated: it could be around 20% in blue sharks in the Canadian fishery.…”
Section: Discussionsupporting
confidence: 76%
“…For pelagic elasmobranchs captured in longline fisheries, previous studies addressing hooking mortality have focused mainly on the blue shark (Prionace glauca). Campana et al (2009) carried out a comprehensive study of blue shark caught in the NW Atlantic (Canadian fishery), including both the short-term hooking mortality recorded at haulback and the post-release longterm mortality recorded by satellite telemetry. Also in the NW Atlantic, Diaz and Serafy (2005) analysed factors that could affect the numbers of blue sharks in good enough condition for live release, using data from the U.S. Atlantic pelagic fishery observer program.…”
Section: Introductionmentioning
confidence: 99%
“…Lewison et al (2004) used a rigorous grid approach to estimate 206 million hooks in the North Atlantic, but noted that more of the effort was directed at tuna rather than swordfish (swordfish-directed sets tend to catch more blue sharks than tuna-directed sets). Campana et al (2009) reported a similar value for North Atlantic effort of 212 million hooks. ICCAT (2012) reported 135 million hooks for the North Atlantic in 2006; however, this value of effort came only from vessels that reported catch-effort data (T2 data) and ignored vessels that reported only catch (T1 data).…”
Section: Estimation Of Shark Catchsupporting
confidence: 60%
“…Although the implementation of these measures can often result in higher discards, postrelease survival rates of pelagic sharks are relatively high (65%; ref. 33), emphasizing that catch quotas/size limits may well be the simplest option to regulate/limit pelagic shark catches in international waters. Therefore, greater international efforts are needed to approach implementation of regulations aimed at limiting the catches of pelagic sharks by longlining fishing vessels that we have found to overlap their preferred habitats almost entirely.…”
Section: Discussionmentioning
confidence: 99%